Discontinuation of statins in a population of older New Zealanders with limited life expectancy. Issue 4 (7th April 2016) - Nishtala, P. S.; Gnjidic, D.; Chyou, T.; Hilmer, S. N.
Abstract : Discontinuation of statins may be considered for older individuals with a cancer, multi‐morbidity, approaching end‐of‐life and in primary prevention. The aim of this study is to investigate the relationship between the rates of statin discontinuation in the last 12 months of life and a diagnosis of cancer, and in individuals using statins for primary or secondary prevention. A case–control study of matched cases and controls. Matching was based on age, Charlson comorbidity index scores and socioeconomic status. Prescription and diagnostic data for 20 482 individuals who were aged over 75 years, were in their last 12 months of life and were receiving statins during the study period (1 January 2007 to 31 December 2012). After propensity score matching, we identified 4832 cases with a diagnosis of cancer and 4809 matched controls. We used Cox regression to test the relationship between the relative risk of statin discontinuation and a diagnosis of cancer, and in individuals using statins for primary or secondary prevention. Statins were discontinued in 70.4% of older adults with a diagnosis of cancer and 55.8% of those without cancer ( P < 0.05). The Cox regression analysis supports that a diagnosis of cancer can increase the rate of statin discontinuation compared with individuals without a diagnosis of cancer regardless of whether statins were used for primary or secondary prevention ( P < 0.05). The findings from this study support that statins are likely to be discontinued in the last year of life in older people with limited life expectancy from cancer, even if statins were indicated for secondary prevention of cardiovascular disease.